2013
DOI: 10.1021/ic4018739
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide-Based Imaging of Protein–Protein Interactions in Live Cells

Abstract: In order to deduce the molecular mechanisms of biological function, it is necessary to monitor changes in the sub-cellular location, activation and interaction of proteins within living cells in real time. Förster resonance energy transfer (FRET)-based biosensors that incorporate genetically encoded, fluorescent proteins permit high spatial resolution imaging of protein–protein interactions or protein conformational dynamics. However, non-specific fluorescence background often obscures small FRET signal change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
54
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 131 publications
0
54
0
Order By: Relevance
“…In recent years, investigators have made several efforts to develop emissive Tb(III) and Eu(III) complexes for similar types of intracellular imaging and sensing applications (4)(5)(6)(7)(8)(9). These efforts sought to leverage two key features of lanthanide luminophores: 1) millisecond-scale excited-state lifetimes, and 2) multiple narrow (<10 nm, half-maximal) emission bands that span the visible spectrum.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, investigators have made several efforts to develop emissive Tb(III) and Eu(III) complexes for similar types of intracellular imaging and sensing applications (4)(5)(6)(7)(8)(9). These efforts sought to leverage two key features of lanthanide luminophores: 1) millisecond-scale excited-state lifetimes, and 2) multiple narrow (<10 nm, half-maximal) emission bands that span the visible spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported both time-gated and steady-state imaging of responsive lanthanide sensors in living cells, including sensors for Zn 2þ , bicarbonate, pH, and singlet oxygen (21)(22)(23)(24). Lanthanide biosensors may be designed as responsive probes that exhibit an analyte-dependent change in emission intensity or lifetime (6), or as FRET-based systems that use Tb(III) or Eu(III) complexes as donors and FPs, organic dyes, or even quantum dots as acceptors (8,25). The lanthanidebased FRET approach can detect interactions between donor-labeled and acceptor-labeled proteins (via a so-called dual-chain biosensor) or conformational changes of a single protein labeled with both a lanthanide donor and a fluorescent acceptor (via a single-chain biosensor).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3]. The organic ligands can not only well protect the lanthanide ions from vibrational coupling but also increase the light absorption cross section, which makes LnCs more efficient emission compared to single lanthanide ions [4].…”
Section: Introductionmentioning
confidence: 99%
“…The solvent anhydrous ethanol (EtOH) and N,N 0 -Dimethylformamide (DMF) were used after desiccation with anhydrous calcium chloride. The organic polymer poly (methyl methacrylate) (PMMA) was synthesized in situ according to the previous report [1]. Eu 2 O 3 were purchased from Shanghai Yuelong Company.…”
Section: Introductionmentioning
confidence: 99%